The Analgesic Effectiveness of Ipsilateral Transversus Abdominis Plane Block in Adult Patients Undergoing Appendectomy: A Prospective Randomized Controlled Trial - Ghimire, A; Bhattarai, B.; Prasad, J.N.; Shah, S.P. (Kathmandu University Medical Journal, 2017)
Background Transversus abdominis plane block (TAP) has been shown to produce effective pain relief following lower abdominal surgeries but is yet to be routinized in different type of surgeries including appendectomy. The main risk of visceral injury can be logically avoided when the block is performed with the abdomen open using landmark technique in the absence of ultrasound guidance. Objective To assess the effectiveness of TAP block with bupivacaine for postoperative analgesia using landmark technique (performed with the abdomen open) in adult patients undergoing appendectomy. Method Forty patients undergoing appendectomy were randomized to undergo ipsilateral TAP block with bupivacaine (n=20) versus control (n=20) in addition to standard postoperative analgesia. All patients received standard general anaesthesia. The block was performed using the landmark technique with 20 ml of 0.5% bupivacaine or isotonic saline on ipsilateral side just before abdominal closure. Pain severity was measured using Visual Analogue Scale (VAS). Tramadol 50 mg was administered as rescue analgesic intravenously when VAS was four or more postoperatively. The duration of analgesia and the requirement of tramadol in 24 hours postoperatively were recorded. Result Mean duration of analgesia in the TAP block with bupivacaine was longer as compared with placebo (724.00±299.07 min vs 168.25±55.18 min; p< 0.01). The TAP block with bupivacaine compared with saline significantly reduced postoperative VAS pain scores. Mean tramadol requirement in the first 24 hours was also reduced (42.50±37.25 mg vs 120.00±55.18 mg; p<0.01). There were no significant complications attributable to the TAP block. Conclusion Ipsilateral TAP block with bupivacaine using landmark technique with the abdomen open in appendectomy provides effective postoperative analgesia and opioids sparing effect.